Analisis Pengaruh Kinerja Keuangan terhadap Pertumbuhan Laba Pada Sektor Kesehatan yang Terdaftar di BEI Tahun 2020-2022 (per kuartal) - Mega Ayu Lestari; Dwi Eko Waluyo (International Forum of Researchers and Lecturers, 2024)
Profit growth is important for businesses as it can be used to forecast future business plans. Earnings growth is difficult to separate from the company's financial performance as measured by financial ratios. This study aims to determine the effect of accounts receivable turnover ratio, current ratio, debt to equity ratio, and inventory turnover on profit growth. This study has a population of 17 companies over three years (per quarter), and a sample of 204 collected through purposive sampling method, and this study uses data analysis methods, namely multiple regression analysis and panel data with Eviews 12 software. The analysis shows that ITR has a positive and significant effect on earnings growth (Ln), while RTR, CR, and DER have no effect on earnings growth (Ln). All independent variables, namely RTR, CR, DER, and ITR, affect earnings growth (Ln) simultaneously. Earnings growth (Ln) is influenced by the four independent variables by 9%. This shows the capability of financial ratios in anticipating profit increases and can influence investor investment decisions.